IMAGE AND SERVICE ACCESSORIES: THE EFFECT ON CUSTOMER LOYALTY - Muhammad Adnan; Ana Fitria; Maulidia Agustina (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2023)
Traditional use of the word "loyalty" refers to a customer's commitment to certain banking-related goods or brands. This research intends to assess the influence of image and service accessories on customer loyalty at the Singkil Branch of PT. Bank Aceh Syariah. All clients of the Bank Aceh Syariah Singkil Branch are the population for this associative quantitative study, and the sample approach is accidental sampling. A questionnaire with a Likert scale that was evaluated for validity and reliability was used to gather data. The findings of multiple linear regression analysis reveal that image and accessories have a considerable influence on consumer loyalty, either concurrently or separately. These findings emphasize the significance of a favorable image and appealing service accessories in fostering customer loyalty at the PT. Bank Aceh Syariah Singkil Branch. The implication is that businesses must continually monitor the image they convey to their clients and assure the provision of appealing service accessories.